1999
DOI: 10.1126/science.286.5440.790
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of T Cells Mediated by Ca 2+ -Induced Release of the Transcription Factor MEF2

Abstract: T cell receptor (TCR)-induced apoptosis of thymocytes is mediated by calcium-dependent expression of the steroid receptors Nur77 and Nor1. Nur77 expression is controlled by the transcription factor myocyte enhancer factor 2 (MEF2), but how MEF2 is activated by calcium signaling is still obscure. Cabin1, a calcineurin inhibitor, was found to regulate MEF2. MEF2 was normally sequestered by Cabin1 in a transcriptionally inactive state. TCR engagement led to an increase in intracellular calcium concentration and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
230
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(237 citation statements)
references
References 19 publications
7
230
0
Order By: Relevance
“…MEF2 is a transcription factor that has been shown to be activated by p38 MAP kinase through phosphorylation (Yang et al, 1999;Zhao et al, 1999aZhao et al, , 2000aHan and Molkentin, 2000). MEF2 is reported to regulate the transcription of the orphan receptor TR3 (nur77) (Youn et al, 1999Kasler et al, 2000;Liu et al, 2001). We have found that there is a direct link between the activation of MEK and subsequent activation of p38 with the phosphorylation of MEF2 (Holmes et al, 2003b).…”
Section: Mitochondria Are Targets Of Synthetic Retinoid Induced Apoptmentioning
confidence: 55%
“…MEF2 is a transcription factor that has been shown to be activated by p38 MAP kinase through phosphorylation (Yang et al, 1999;Zhao et al, 1999aZhao et al, , 2000aHan and Molkentin, 2000). MEF2 is reported to regulate the transcription of the orphan receptor TR3 (nur77) (Youn et al, 1999Kasler et al, 2000;Liu et al, 2001). We have found that there is a direct link between the activation of MEK and subsequent activation of p38 with the phosphorylation of MEF2 (Holmes et al, 2003b).…”
Section: Mitochondria Are Targets Of Synthetic Retinoid Induced Apoptmentioning
confidence: 55%
“…3) [25,74,76,77]. Activation of T-cell receptors disrupts the interaction of MEF2-D with HDAC4 and Cabin-1, most probably through a Ca 2ĂŸ signal and CaM activation.…”
Section: Biological Roles Of Class Iia Hdacsmentioning
confidence: 99%
“…One of the factors whose genetic ablation causes morphological and transcriptional abnormalities during early cardiogenesis is MEF2C. It is a member of the small MEF2 family of MADS-box containing transcription factors that have been implicated in several fundamental processes including myogenesis, fibertype specification, cardiac hypertrophy, atherosclerosis, and as both an activator and inhibitor of apoptosis (Molkentin et al, 1995;Woronicz et al, 1995;Firulli et al, 1996;Kolodziejczyk et al, 1999;Mao et al, 1999;Youn et al, 1999;Okamoto et al, 2000;Passier et al, 2000;Wu et al, 2000;Dunn et al, 2001;Yan et al, 2001). Deletion of the mef2c gene results in a heart with a small, nonlooping LV, loss of the RV, no trabeculation, and decreased expression of several cardiac-specific genes (Lin et al, , 1998Bi et al, 1999;Bruneau et al, 2000;Liu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%